A new method and device for detecting rebars in concrete based on capacitance. (October 2022) - Han, Xiaofeng; Li, Gege; Wang, Penggang; Chen, Zhaoyi; Cui, Dongbo; Zhang, Hai; Tian, Li; Zhou, Xiangming; Jin, Zuquan; Zhao, Tiejun
Highlights: New method and device were established and validated for the detection of rebars in concrete. Based on the detected capacitance, the position of the rebar in a concrete member can be located. The relationships among capacitance, rebar diameter, and concrete cover were established. The 3D diagrams of the peak value of capacitance, the capacitance area, and rebar diameter or cover thickness were built to detect rebar parameters. Abstract: This study aims at developing a convenient and efficient rebar detection method based on capacitance that can be used to precisely locate the state (i.e., diameter and position) of the rebars in concrete. Finite element analysis was used to optimize the electrode of the capacitive sensor and verify that using the developed capacitive sensor to detect rebar in concrete is feasible and reliable. Based on the detected capacitance, the position of the rebar in concrete can be located. The relationships among capacitance, rebar diameter, and cover thickness are explored. Both the peak value and the peak area of capacitance evolve linearly with rebar diameter and exponentially with cover thickness. The 3D diagrams among the capacitance peak value, peak area, and rebar diameter or cover thickness are established in this research. The experimental result agrees well with the numerical results, which verifies the reliability of the capacitive sensor and detection methods established.